Evaluation of the Sealing Ability of Amalgam, MTA, Portland Cement and Coltozol in the Repair of Furcal Perforations - Ahangari, Zohreh; Karami, Mahdieh (Iranian Endodontic Journal, 2008)
INTRODUCTION: Perforations of the pulpal floor create problems during endodontic treatment and often results in secondary periodontal involvement with eventual loss of teeth. The purpose of this study was to evaluate the ability of mineral trioxide aggregate (MTA), Amalgam, zinc oxide and eugenol (ZOE) and Portland cement to seal furcal perforations in extracted human molars using dye penetration. MATERIALS AND METHODS: This Microleakage study was conducted on 70 human permanent mandibular molars with well developed, non-fused roots. Access openings and furcation perforations were prepared in the pulp chamber floor. Ten teeth were assigned as controls and divided into two groups of five teeth each as positive and negative control. The positive group were accessed and perforated similar to experimental groups but the negative controls were not prepared. The rest of the teeth were divided in four experimental groups of 15 teeth in each group. Experimental groups comprised groups Al to A4, group Al was repaired with MTA, group A2 with Amalgam, group A3 with Coltozol (ZOE) and group A4 was repaired with Portland cement. The teeth were submerged in solution of 2% fucshin dye for 24 hours. Finally, the samples were sectioned and evaluated for linear dye leakage at X25 magnification and analyzed statistically. RESULTS: The results showed that MTA had significantly less leakage than Amalgam, Portland cement and Coltozol (P<0.05). CONCLUSION: Maximum dye penetration was observed in Coltozol followed in decreasing order by Portland cement and Amalgam.